Ciliary IFT80 is essential for intervertebral disc development and maintenance. Issue 5 (30th March 2020) - Li, Xinhua; Yang, Shuting; Han, Lin; Mao, Keya; Yang, Shuying
Abstract: The intervertebral disc degeneration (IVDD)‐related diseases occur in more than 90% of the population older than 50 years. Owing to the lack of understanding of the cellular mechanisms involved in IVDD formation effective treatment options are still unavailable. Primary cilia are microtubule‐based organelles that play important roles in the organ development. Intraflagellar transport (IFT) proteins are essential for the assembly and bidirectional transport within the cilium. Role of cilia and IFT80 protein in intervertebral disc (IVD) development, maintenance, and degeneration are largely unknown. Using cilia‐GFP mice, we found presence of cilia on growth plate (GP), cartilage endplate (EP) annulus fibrosus (AF), and nucleus pulposus (NP) with varying ciliary length. Cilia length in NP and AF during IVDD were significantly decreased. However, cilia numbers increased by 63% in AF during repair. Deletion of IFT80 in type II collagen‐positive cells resulted in cilia loss in GP and EP, and disrupted IVD structure with disorganized and decreased GP, EP, and internal AF (IAF), and less compact and markedly decreased gel‐like matrix in the NP. Deletion of IFT80 in type I collagen‐positive cells led to a disorganized outer AF (OAF) with thinner, loosened, and disconnected fiber alignment. Mechanistic analyses showed that loss of IFT80 caused a significant increase in cell apoptosis in the IVD, and a marked decrease in expression of chondrogenic markers ‐ type II collagen, sox9, aggrecan, and hedgehog (Hh) signaling components, including Gli1 and Patch1 in the IVD of IFT80 fl/fl ; Col2‐creERT mice, and Gli1 and Patch1 expression in the OAF of IFT80 fl/fl ; Col1‐creERT mice. Interestingly, Smoothened agonist‐SAG rescued OAF cell proliferation and osteogenic differentiation. Our findings demonstrate that ciliary IFT80 is important for the maintenance of IVD cell organization and function through regulating the cell survival and Hh signaling.